L'intérêt de la DVP pour (re)donner du sens aux apprentissages - Olivier Blond-Rzewuski
The fight against social and school inequalities requires rethinking the relationship to knowledge. Teaching philosophy for children can be considered as a lever to reflect on the meaning of the word "learning" by developing their posture as learner. This article is based on a long teaching experience within the French elementary school system and more specifically with children living in "priority education zones" (the "REP +" zones). The discussion with a philosophical purpose ("DVP") can be a tool for other disciplinary fields and is proving to be a vector of the desire to learn for children children who are particularly vulnerable academically and socially. Philosophy is therefore seen as a "learning modality". Through an original approach, with Lipmannian connotation, the goal is to promote or develop the "student posture" of pupils, somewhat using a pedagogy of astonishment or enigma. An illustration of this approach is proposed as part of reading in Cycle 3.